(untitled) (Research Announcements "Heritage BG", 2025)
The article is devoted to the establishment and functioning of outpatient medical care – an important element of the Balkan national health systems in the late 19th and early 20th centuries. A special focus is put on the case of Bulgaria. The establishment of a network of outpatient clinics and their activities is examined and an attempt is made to define their place and importance in the national health system. References: Belinov 1937: Belinov, Stoyan. Kam istorijata na Aleksandrovskata bolnitsa 1884 – 1934. Sofia. Kolarov 1878: Kolarov, Nikola. Iz istoriyata na zhelezopatnata meditsinska sluzhba v Balgarija 1888 – 1944. Meditsina i fizkultura. Sofia. Konstantinov 2022: Konstantinov Nikola. Istorija na zdraveopazvaneto v Balgarija 1878 – 1952. Faber. Sofia. Meditsinski sbornik 1898: Meditsinski sbornik. Pechatnitsa ‘Valkov’. Sofia. Nazarska 1994: Nazarska, Georgeta. Sanitarnoto delo v Iztochna Rumeliya, 1879 – 1885. – Asklepios. Mezhdunaroden godishnik po istoriya i obshta teoriya na meditsinata, No. 8, 80-91. Russev 1904: Russev, Мarin. Yubileyna kniga. In: Istoricheski pregled na meditsinskata chast i meditsinskata knizhnina v Balgariya: 15 avgust 1878 – 15 avgust 1903 (ed. Marin Russev). K. Chinkov. Sofia. Sofiiskoto okrazhie 1898: Izlozhenie za sastoyanieto na Sofiiskoto okrazhie prez 1897 – 1898 g. Sofia 1898. Sofia. Statisticheski godishnik 1910-1915: Statisticheski godishnik na Balgarskoto Tsarstvo za 1909 – 1912 g. Darzhavna pechatnitsa. Sofia. Svishtovskoto okrazhie 1895: Izlozhenie za sastoyanieto na Svishtovskoto okrazhie prez 1894 – 1895 g. Svishtov. Transkoto okrazhie 1898: Izlozhenie za sastoyanieto na Transkoto okrazhie prez 1897 – 1898 g. Sofia 1898. Sofia. Vracheva 2020: Vracheva, Penka. Profesiya meditsinski feldsher v Balgariya. Vaznikvane i razvitie do nashi dni. Sayuz na uchenite – Stara Zagora. Stara Zagora. Bournova 2008: Bournova Eugenia. La mortalité en transition dans une ville méditerranéenne Rethymno au début du XXe siècle. – Histoire urbaine, No. 21, 1, 5-35. Čubrilović 1974: Čubrilović, Vaso. Istorija Beograda. 2. Srpska akademija nauka i umetnosti. Beograd. Davidova 2018: Davidova, Evgenija. Serving the State: Military and Public Health Practices in Bulgaria (1878 – 1908). – European History Quarterly, № 48(4), 686 – 707. Kostov 2023: Kostov, Alexandre. Health Systems in the Balkans at the End of the 19th and the Beginning of the 20th Century on the Case of Bulgaria and Serbia (Comparative Analysis). – Études Balkaniques, No. 61, 100 – 118. Sundhaussen 1989: Sundhaussen, Holm. Historische Statistik Serbiens 1834 – 1914: Mit europдischen Vergleichsdaten. Sьdosteuropдische Arbeiten. Oldenbourg Verlag. München. Şuta, Tămaş, Ciupală, Bărbulescu, Popovici 2009: Şuta, Alina Ioana, Oana Mihaela Tămaş, Alin Ciupală, Constantin Bărbulescu, Vlad Popovici. Legislaţia sanitară în România modernă (1874 – 1910). Presa Universitara Clujeana. Cluj-Napoca. Turda 2012: Turda, Marius (Guest Editor). Private and Public Medical Traditions in Greece and the Balkans. – Deltos: Journal of the History of Hellenic Medicine, special issue, 3-6.